المساندة الاجتماعية النفسية وعلاقتها بالصلابة النفسية لدى عينة من المتعافين من فيروس كورونا في محافظة الوسطى - غزة - مونس، خالد عوض عبدالله (جامعة القدس المفتوحة, 2022)
هدفت الدراسة التعرف إلى مستوى المساندة الاجتماعية النفسية ومستوى الصلابة النفسية، والعلاقة بينهما، ومعرفة مدى اختلاف مستوى كل منها باختلاف متغير؛ (العمر، والحالة الاجتماعية، والمستوى التعليمي) لدى عينة من المتعافين من فيروس كورونا في محافظة الوسطى، واستخدمت الدراسة المنهج الوصفي الارتباطي، ولتحقيق أهدافها طور مقياسان كأداتين للدراسة (مقياس المساندة الاجتماعية النفسية، ومقياس الصلابة النفسية)، وبعد التأكد من صدقهما وثباتهما، طبقا على عينة متيسرة مكونة من (123) من المتعافين من فيروس كورونا في محافظة الوسطى، وبعد تحليل البيانات، توصلت الدراسة إلى أن مستوى المساندة الاجتماعية النفسية جاء بمستوى متوسط، ومستوى الصلابة النفسية بمستوى مرتفع، وأن هناك علاقة ارتباطية طردية موجبة بين درجة المساندة الاجتماعية والصلابة النفسية، وعدم وجود فروق في المساندة الاجتماعية النفسية تعزى لمتغير المستوى التعليمي، ووجود فروق في المساندة الاجتماعية النفسية تعزى لمتغيرات العمر، والحالة الاجتماعية، وعدم وجود فروق في الصلابة النفسية تعزى لمتغير الحالة الاجتماعية، ووجود فروق في الصلابة النفسية تعزى لمتغيري العمر، والمستوى التعليمي لدى المتعافين من فيروس كورونا، وفى ضوء نتائج الدراسة ومناقشتها أوصت الدراسة بضرورة تصميم برامج إرشادية تستهدف المتعافين من فيروس كورونا، وتوفير الرعاية النفسية والاجتماعية لهم. The study aimed to identify the level of psychosocial support and psychological toughness, the relationship between them, and the extent of difference of each according to the variables of age, marital status, and educational level. The study was applied to a recovered sample from COVID-19 in al-Wusta governorate. The study employed the descriptive correlative approach. To achieve its objectives, two scales were developed as study tools, the psychosocial support scale, and the psychological toughness scale. After checking their validity and reliability, they were applied to 123 recovered persons from COVID-19 in al-Wusta Governorate. After analyzing the data, the study concluded that the level of psychosocial support came at an average level, and the level of psychological toughness came at a high level. There is a positive direct correlation between the degree of social support and psychological toughness. There are no differences in the psychosocail support due to the variables of the educational level, age and social status. There are no differences in psychological toughness due to the variable of social status, age and educational level of those recovered from COVID-19. In light of the results of the study and its discussion, the study recommended the necessity of designing counseling programs targeting the recovered from COVID-19 and provide them with psychological support and social care.
Keywords: المساندة الاجتماعية -- المساندة النفسية -- الصلابة النفسية -- المتعافين من كورونا -- فيروس كورونا (كوفيد-19) -- محافظة الوسطى -- فلسطين